Measurements of triple-differential cross sections for inclusive isolated-photon+jet events in p p collisions at s = 8 TeV - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Asilar, E; Bergauer, T; Brandstetter, J; Dragicevic, M; Erö, J; Del Valle, A Escalante; Flechl, M; Frühwirth, R; et al. (The European physical journal. C, Particles and fields, 2019)
Measurements are presented of the triple-differential cross section for inclusive isolated-photon+jet events in p p collisions at s = 8 TeV as a function of photon transverse momentum ( p T γ ), photon pseudorapidity ( η γ ), and jet pseudorapidity ( η jet ). The data correspond to an integrated luminosity of 19.7 fb - 1 that probe a broad range of the available phase space, for | η γ | < 1.44 and 1.57 < | η γ | < 2.50 , | η jet | < 2.5 , 40 < p T γ < 1000 GeV , and jet transverse momentum, p T jet , > 25 GeV . The measurements are compared to next-to-leading order perturbative quantum chromodynamics calculations, which reproduce the data within uncertainties.